2015
DOI: 10.1016/j.ijrefrig.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

An efficient numerical scheme for the simulation of parallel-plate active magnetic regenerators

Abstract: A one-dimensional model of a parallel-plate active magnetic regenerator (AMR) is presented in this work. The model is based on an efficient numerical scheme which has been developed after analysing the heat transfer mechanisms in the regenerator bed. The new finite difference scheme optimally combines explicit and implicit techniques in order to solve the one-dimensional conjugate heat transfer problem in an accurate and fast manner while ensuring energy conservation. The present model has been thoroughly vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In addition to the validation of the numerical model, the authors highlighted problems related to hydraulic losses as one of the important issues requiring further attention. In 2015, Torregrosa‐Jaime et al proposed a new finite‐difference model that optimally combined explicit and implicit techniques for solving 1D transient heat transfer in an active magnetic regenerator. The model substantially reduced the calculation time compared with previous similar models.…”
Section: Magnetocaloric Refrigeration and Heat Pumpingmentioning
confidence: 99%
“…In addition to the validation of the numerical model, the authors highlighted problems related to hydraulic losses as one of the important issues requiring further attention. In 2015, Torregrosa‐Jaime et al proposed a new finite‐difference model that optimally combined explicit and implicit techniques for solving 1D transient heat transfer in an active magnetic regenerator. The model substantially reduced the calculation time compared with previous similar models.…”
Section: Magnetocaloric Refrigeration and Heat Pumpingmentioning
confidence: 99%
“…Implicit methods have also been used in both systems, namely the Crank–Nicholsen method, 118,148 Runge–Kutta method, 139 backward Euler method, 162 and alternate direction implicit temporal integration method 110 . It was shown that explicit methods are more appropriate when the computational resources are reduced, while implicit methods are more suited when the accuracy is regarded as the most important feature 110,144,163 …”
Section: Numerical Implementationmentioning
confidence: 99%
“…This emerging technology bases its operation on the magnetocaloric effect (MCE), which is a physical phenomenon, related to solid-state materials with magnetic properties. A number of numerical models have been executed in order to improve the MCE and physical procedures related to the operation of reciprocating AMRs [11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Some of those studies [15][16][17][18][19]24] aimed to create one-dimensional transient thermal models without solving the fluid flow problem. Other models considered 2D heat exchange in the magnetic material under a different methodology.…”
Section: Introductionmentioning
confidence: 99%